Effective of Reading Pictures Entrance in Development of Reading Understanding & Live Activities through Arabic language course (Lughti Al-Jamila) for Primary Sixth Female Students - Alabdali, Najmah Abdulmoen (Journal of Educational and Psychological Sciences, 2021)
This study aimed to know the effectiveness of the image- reading approach in developing reading comprehension and life skills in Arabic language course (lughti aljamila) for sixth- grade primary students in the Al- Baha region in the Kingdom of Saudi Arabia. The researcher used quasi- experimental approach to achieve the goal of the study, and to find out the effect of the experimental factor (the effectiveness of the image reading approach) on (developing reading comprehension and life skills) on the experimental group. The study tool has been prepared and represented in the achievement test, where the students were divided into two groups, the experimental group, which will be applied to the study, composed of (37) students, and the control group consisted of (37) students. The study’s result showed the following: 1) The study reached (23) reading comprehension skills needed for sixth graders in a course in my Arabic language in Al Baha schools (Al Baha city), it was included in five main areas, namely; (Literacy comprehension skills, literal deduction skills, critical comprehension skills, taste comprehension skills, creative comprehension skills), in addition to the study reaching (10) life skills required for sixth graders in the Arabic language subject in Al Baha region schools. The results of the statistical analysis showed that there are statistically significant differences between the mean scores of female students in the experimental and controlling groups in reading comprehension skills and dimensional life skills in favor of the experimental group, which means that employing the entrance to the images takes a clear effectiveness in the female students’ teaching. The study recommended the following: asking specialists in curriculum planning in the Kingdom of Saudi Arabia to reconsider forming education activities, and work to balance reading comprehension skills and life skills in all areas in a balanced manner and according to a specific methodology.